Perbandingan Kapasitas Pemerintah Daerah dalam Mengelola Dana Otonomi Khusus di Aceh dan Papua - Ahya Riwanda Muharram; Furqan Al Fatin; Dwi Nurazalia; Nurul Kamaly; Zakirah Azman (Indo Publishing, 2026)
Special autonomy in Aceh and Papua was granted to mitigate conflict and accelerate prosperity through substantial authority and funding. However, after two decades, its impact remains debated and has not been evenly felt by the community. The purpose of this study is to analyze differences in local government capacity in managing special autonomy funds and the indicators that influence their effectiveness. The method used in this study was library research, using sources such as journal articles, regulations, planning documents, and audit reports from the Supreme Audit Agency of the Republic of Indonesia in Aceh and Papua. The research